The Impact of Attitude and Subjective Norms towards Zakat Compliance Behavior in Malaysia - Abashah, Aidanazima; Hanie Abu Samah, Irza; Naiemah Saraih, Ummi; Maizura Abd. Rashid, Intan; Nurshahrizleen Ramlan, Sayang; Nor Syafawati W. Muhammad Radzi, Wan (International Journal of Engineering and Technology, 2018)
Zakat always play as an important element for Muslims and it is the funding for Muslims community itself. The completion of this study will help to understanding the zakat concept among Muslim community in Malaysia and at the same time will increase the collection of zakat by zakat institution for Muslim development purpose. The effect of attitude and subjective norms towards zakat compliance behavior are the focus to be investigated further in this research. The study was done among government servant in Malaysia by using a quantitative approach. 200 questionnaires were administrated among various level of government servant in Malaysia. Next, the data were analyzing by using SPSS Software. Correlation analysis and regression analysis were perform, thus the result indicates that attitude (r=0.417, sig=0.000, p<0.01) shows the highest of positive significant result towards zakat compliance behavior compared to other variable subjective norms (r=0.752, sig=0.305, p>0.05). This research warrant more investigation upon zakat compliance behavior and other variables. Thus, it has been shown that attitude give a significant relationship with zakat compliance behavior.